Upgrading petroleum residues and heavy oils - Gray, Murray R (Chemical industries (Marcel Dekker, Inc.), 1994)
"This useful reference offers in-depth coverage of current techniques for converting heavy oils and residues into more valuable distillates.Examines the chemistry of heavy hydrocarbon feeds and their properties important to engineering design, including phase behavior, reaction kinetics, and thermodynamic and transport characteristics!"